Women's Age at First Marriage and Marital Instability in the United States: Differences by Race and Ethnicity - Evelyn L. Lehrer; Yeon Jeong Son (Institute of Labor Economics (IZA), 2017)
The age at which women enter first marriage is known to be a major factor in marital instability. But to date possible differences by race/ ethnicity have not been examined. We use data from the 2006-2010 National Survey of Family Growth to examine differences by race/ethnicity in the shape of the curve relating women's age at entry into first marriage to marital instability. We find that for non-Hispanic white women, the probability of dissolution falls with age up to ages 30-32 and thereafter the curve flattens out. For black women, marital instability decreases with age only up to ages 24-26. For Hispanic women, marital instability falls from age ≤20 to 21-23 and then the curve flattens out; beyond ages 30-32 the curve turns upward. We suggest explanations for these patterns based in part on differentials in the associations of age at marriage with education and non-marital fertility. For white women, but not for their black and Hispanic counterparts, delayed entry into marriage is associated with a small increase in non-marital fertility and a pronounced increase in education. The common practice in the demographic literature in the U.S. of conducting pooled analyses with simple controls for black, Hispanic, and other can lead to misleading conclusions. Our findings underscore the desirability of conducting separate analyses by race / ethnicity wherever possible.
Keywords: J12; 330; divorce; marital dissolution; marital instability; family structure; race/ethnicity